Factors of the emergence and spread of radicalism and terrorism in the Islamic world - Bagheri Seyed Kazem Seyed (Kom: Časopis za Religijske Nauke, 2021)
Referring to the current literature of radicalism and terrorism, we can find a variety of its aspects that unfortunately deal with all spheres of public life in thought, politics, society and economics and have a negative impact on international relations; all these matters show the importance of understanding the roots of radicalism and its rising. This writing tries to find the bases, contexts and factors of radicalism rising and its formation, especially in the Muslim world. The purpose of this study is to search the thinking infrastructure and factors of appearance and emersion of radicalism and terrorism, so, the main question of this study is to examine the context, background and factors of radicalization and the emergence of the idea in Islamic community. Despite all teachings of Holly Qur'an, the value of immunity and protection of human lives, what happened to so-called Moslems that without fear and without regard to their own lives kill and harm themselves, women, children and innocent people. In response to the question , this hypothesis presents that Factors can be divided into two parts: theoretical-intellectual and sociological factors, In the section on theoretical intellectual factors some factors such as non-comprehensive and wrong analysis of holly texts; overcoming feelings and emotions over reason and rationality; feeling of injustice and unfair, despairing from current situation and having no hope to improve and reform, and in sociological section, some factors, such as utilization from extremism as an instrument in foreign relations by some super powers, poverty, incorrect foreign relations of some super powers and processes of globalization, are some important grounds and factors that lead to radicalism extension in recent decades. This study was conducted according to the sociology of knowledge.